Efficient Charge Transfer in Z‐Scheme g‐C3N4/Cu/MoS2 Heterojunctions for Enhanced Photocatalysis and Photoenhanced Electrocatalysis. Issue 25 (10th August 2022) - Zhu, Kaili; Wang, Chuanjie; Luan, Xinxin; Li, Jia; Yang, Ping
Abstract: Efficient charge separation and transfer is always an important prerequisite for efficient photocatalysis. Herein, g‐C3 N4 /Cu/MoS2 Z‐scheme heterojunctions are successfully constructed by a two‐step calcination method, in which Cu nanoparticles are embedded as an electronic conductor between g‐C3 N4 and MoS2 . g‐C3 N4 /Cu/MoS2 composites reveal excellent photocatalytic activity. The rate of hydrogen production reaches to 970.5 µmol g −1 h −1, which is 22 and 2.63 times of that of g‐C3 N4 and g‐C3 N4 /MoS2, respectively. Meanwhile, due to the significant enhancement of the conductivity of g‐C3 N4 /Cu/MoS2 and the efficient charge transfer, its electrocatalytic hydrogen evolution activity is also far superior. In addition, the electrocatalytic activity of g‐C3 N4 /Cu/MoS2 under light irradiation is significantly improved compared with that under dark condition. This is ascribed to the decrease of charge transfer resistance in the Z‐scheme system during light irradiation. The photochemical and electrochemical properties of g‐C3 N4 /Cu/MoS2 composites are compared with those of g‐C3 N4 /MoS2, which illustrate that the construction of g‐C3 N4 /Cu/MoS2 Z‐scheme heterojunction is an important factor to increase the charge transfer rate. The result provides a new idea for the realization of efficient charge transfer and the synergistic catalytic of photo and electro for water decomposition. Abstract : A non‐noble metal g‐C3 N4 /Cu/MoS2 Z‐scheme heterojunction is prepared to get enhanced photo and electro catalysis performance. The Z‐scheme system greatly increases the charge transfer kinetics, effectively inhibits the recombination of charge and hole, and enhances the photoelectric synergy ability, the photocatalytic hydrogen production rate of which reaches 970.7 µmol g −1 h −1 without Pt as cocatalyst.